If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7p + -3p + 6 = -4p + 10 Reorder the terms: 6 + 7p + -3p = -4p + 10 Combine like terms: 7p + -3p = 4p 6 + 4p = -4p + 10 Reorder the terms: 6 + 4p = 10 + -4p Solving 6 + 4p = 10 + -4p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '4p' to each side of the equation. 6 + 4p + 4p = 10 + -4p + 4p Combine like terms: 4p + 4p = 8p 6 + 8p = 10 + -4p + 4p Combine like terms: -4p + 4p = 0 6 + 8p = 10 + 0 6 + 8p = 10 Add '-6' to each side of the equation. 6 + -6 + 8p = 10 + -6 Combine like terms: 6 + -6 = 0 0 + 8p = 10 + -6 8p = 10 + -6 Combine like terms: 10 + -6 = 4 8p = 4 Divide each side by '8'. p = 0.5 Simplifying p = 0.5
| 3y-10-2y=2 | | -3x(20x+12)=O | | 10z-.40=1.70 | | (4c-5)(7c-2)= | | 7x+38=59 | | 35=6v+v | | 3/13+8/26+7/13= | | 10x+.40=2.40 | | -(8+13)+3m=2(2m-11-3m) | | (4x^2y^3-6y^2+5x^3)-(3x^3Y^2+x^3-2x^2y^3)= | | 3-x(20x+12)=0 | | -3.7+2.4x=0 | | 2w-2=-9+3w | | 900=2X*55 | | -9d=1-8d | | 8=3(3x-0) | | -v-8=3v | | -2x=y+4 | | y+10-7y=-5(y-4) | | 5(2n+6)=-4(-5-2x)+3x | | G=2g-7 | | 3(-6-7v)= | | 12(b+3)=4(3b+3)+3b | | -2n=-3+10 | | 5-3x+4x=-5 | | (-9x^6y^4z)(y^2z^4)= | | 18=-9r | | 2t-0=15 | | 2(1x-3)=2x | | 6y+x=12 | | 36=-12b | | 4a-4=2a+34 |